Analysis of Volleyball Referee Classification On Referee Performance In Sumedang Regency - Saepuloh, Diki; Sudraza, Adang; Dinangsit, Dinar (UNIVERSITAS NEGERI MAKASSAR, 2025)
Referees have an important role in ensuring that volleyball matches are conducted fairly and following applicable rules. In Sumedang Regency, the quality of referee performance is still a debate, especially regarding the influence of referee classification based on certification and experience on their performance on the field. This study aims to explore the relationship between referee classification and their performance in leading volleyball matches. This study uses a qualitative method with a case study approach. Data was collected through interviews with various related parties, including referees, referees, coaches, and players, as well as through field observations and documentation. The data triangulation technique is used to increase the validity and reliability of research results. The results of the study showed that referee performance was classified based on understanding of rules, consistency in decision-making, communication skills, and physical and mental readiness. Referees with higher experience and certifications tend to show better performance in those aspects compared to less experienced referees. In addition, the training and continuous development factor has been proven to contribute to improving the quality of refereeing. The conclusions of this study confirm that the classification of referees plays an important role in determining their performance in leading volleyball matches. Therefore, it is necessary to increase referee capacity through continuous training and periodic evaluations to ensure high referee standards. This research contributes to the understanding of factors that affect referee performance and can be a reference for the development of a more effective certification system and referee coaching.